2000
DOI: 10.1002/etc.5620190410
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organochlorine compounds and extractable organic halogen in three subspecies of ringed seal from Northeast Europe

Abstract: Oganochlorine compounds in blubber samples of the ringed seal (Phoca hispida saimensis, P. h. ladogensis, and P. h. hispida) were analyzed in order to estimate the state of pollution in three different water areas in Northeast Europe, namely, Lake Saimaa in Finland, Lake Ladoga, and the White Sea in Russia. Geographic differences in concentrations and in relative concentrations of tri‐ and tetrachlorocymenes, hexachlorobenzene, α‐HCH, β‐HCH, ‐γ‐HCH (Lindane), seven polychlorinated bi‐phenyl (PCB) congeners, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…However, that phenomenon is not general. In a previous study of ringed seals from Lake Ladoga and Lake Saimaa, β‐HCH was the most abundant form from 1988 to 1995, indicating persistence of this isomer [25]. The termination of use of HCHs in the Lake Saimaa area also is evident from to this study, because only β‐HCH and some traces of lindane were present in ringed seals from the late 1990s.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…However, that phenomenon is not general. In a previous study of ringed seals from Lake Ladoga and Lake Saimaa, β‐HCH was the most abundant form from 1988 to 1995, indicating persistence of this isomer [25]. The termination of use of HCHs in the Lake Saimaa area also is evident from to this study, because only β‐HCH and some traces of lindane were present in ringed seals from the late 1990s.…”
Section: Discussionsupporting
confidence: 55%
“…The proportions of HCHs to ∑HCH in Lake Haukivesi ringed seals that died during the 1980s are similar to those of technical HCH, in which the proportions are 60 to 70% of α‐HCH, 5 to 12% of β‐HCH, and 10 to 15% of lindane [42], except that the proportion of β‐HCH was higher in this study. Many studies have shown the high ratio of α‐HCH in Arctic waters, mainly because of long‐range transport of that isomer [9,25,32,42]. However, that phenomenon is not general.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations